Employment Contracts, Implied Terms and Judicial Law-Making - Hodder, Jack (Victoria University of Wellington Law Review, 2002)
his paper discusses the facilitation and regulation of employment, reflecting an employment perspective that employment is a contractual arrangement which cannot be divorced from a commercial context. The paper also notes that the judicial law-making role is appropriately limited in scope. The author argues the above points through a thorough analysis of the common law development of employment law, in particular the implied term of acting in trust and confidence – including Addis v Gramophone Company, Western Excavating, and the Woods case. The author is not persuaded that the adoption of the implied term has enhanced the clarity or predictable application of the legal rules governing employment contracts. However, the important question is the scope and foundation of judicial law-making in our era – one which helped shape implied terms in employment contracts.